MCA's battle cry : without fear or wisdom? - Choong, Pui Yee (2013)
The Malaysian Chinese Association's cry of "Battle Without Fear" for the coming elections is aimed at the opposition and focuses on cultural issues. It m ay not meet the aspirations of the younger Malaysian electorate who want action on broader issues of equal opportunity and good governance.